Profile of Adolescent Friendship Relationships in West Java Province, Indonesia, and Implications for Guidance and Counseling - Siti Rohimah; Syamsu Yusuf; Ipah Saripah; Eka Sakti Yudha (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This research is motivated by the need for adolescents to be accepted by their social environment. Environmental and peer influences largely shape the formation of adolescent social attitudes and behaviors. These peer relationships facilitate adolescents’ ability to establish friendships. This study aims to collect empirical data on the profile of friendship relationship skills of high school students and their implications for guidance. High School students and their impact on guidance and counseling. The results indicate that the level of friendship-building skills among high school students falls within the low category, with a mean of 208.083 and a standard deviation of 26.411 across interaction skills, empathy, self-disclosure, emotional support, and trust. The profile of male students' ability to establish friendships indicates a lower level of mastery than that of female students. Keywords: adolescent, friendship, guidance and counseling